Efficacy of a brief telemedicine-based cognitive behavioral treatment (BRIGHT) versus attention control for head and neck cancer survivors with body image distress: A randomized trial. Issue 28 (1st October 2022) - Graboyes, Evan Michael; Maurer, Stacey N; Balliet, Wendy; Li, Hong; Williams, Amy M.; Osazuwa-Peters, Nosayaba; Padgett, Lynne; Yan, Flora; Gordis, Tamar; Rush, Angie; Ruggiero, Kenneth J.; Sterba, Katherine R.
Abstract : 212 Background: Nearly 1 in 3 head and neck cancer (HNC) survivors suffer from body image distress (BID), a source of devastating psychosocial morbidity that impairs quality of life. Evidence-based strategies to manage BID among HNC survivors are lacking. This trial evaluates the preliminary efficacy of BRIGHT (Building a Renewed ImaGe after Head & neck cancer Treatment), a brief tele-cognitive behavioral intervention, relative to attention control (AC), at reducing BID among HNC survivors. Methods: HNC survivors with clinically significant BID were randomized to BRIGHT (n = 20) or AC (n = 24). BRIGHT was delivered by a psychologist in 5 weekly video tele-medicine sessions. AC consisted of dose- and delivery-matched survivorship education. Changes in HNC-related BID and cancer-related BID were assessed using the IMAGE-HN and Body Image Scale (BIS), respectively. The effect of BRIGHT vs AC was analyzed using generalized linear models. Clinical response (proportion of patients with a clinically meaningful change in IMAGE-HN and BIS scores) for BRIGHT vs AC was analyzed with logistic regression. Results: The median age was 63 years (range 41-80) and 61% had stage III/IV HNC. BRIGHT decreased HNC-related BID from baseline to 1- and 3-months post-intervention relative to AC (Table). At 3-months post intervention, the response rate of BRIGHT on HNC-related BID was 6.6-fold higher than AC (OR = 6.6; 90% CI 2.0 to 21.8). BRIGHT decreased cancer-related BID from baseline to 3-months post-intervention vs AC (Table). The improvement in HNC-related BID and cancer-related BID for BRIGHT vs AC at 3-months was clinically significant and the effect size was large (Cohen's d = -0.9, 90% CI -1.4 to -0.4 for each). Conclusions: In this pilot RCT, BRIGHT results in clinically meaningful improvements in BID among HNC survivors. These promising preliminary data support conducting a large efficacy trial to establish BRIGHT as the first evidence-based treatment for HNC survivors with BID. Clinical trial information: NCT03831100. Effect of BRIGHT vs AC on HNC-related BID and cancer-related BID. Effect Mean difference (BRIGHT vs AC) 90% CI P-value Δ IMAGE-HN score from baseline 1 mo -8.0 -15.9 to 0.0 0.1 3 mos -17.1 -25.6 to -8.6 0.002 Δ BIS score from baseline 1 mo -2.1 -5.0 to 0.9 0.2 3 mos -5.8 -9.1 to -2.5 0.006 IMAGE-HN score range 0-84, higher scores indicate greater HNC-related BID BIS score range 0-30, higher scores indicate greater cancer-related BID.